Developing English for Specific Purposes (ESP) Courses in IT: A Narrative Experience of the Universidad Técnica Nacional (Revista Electrónica Calidad en la Educación Superior, 2021)
The importance of English and technology for the workplace increases the need of higher education schools to develop and promote English for specific purpose (ESP) programs that provide students with both effective communication competences and digital skills to prepare them for their professional development. Consequently, it has become a great challenge for English educators to look for innovative techniques to improve these two competences based on the activities that are relevant and typical to their profession and context. The preset work aims to share a one-year experience in the design and development of three-course program on English for technology, for the English as a Second Language Program at Universidad Técnica Nacional.
Keywords: ESP; Course Design; Technology; Teaching English; ICT